Clinical Interventions of Critical Care Pharmacist in the Therapeutic Management of Critically Ill Patients: a Retrospective Study in Bangladesh - Hasan, Md Jahidul; Rabbani, Raihan; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Critically ill patients at ICU are treated with poly pharmacy and conservative drug management is necessary for ensuring drugs’ safety and accuracy. The objective of this study was to analyze the qualitative intervention of critical care pharmacists (CCP) in critically ill patients’ effective medication management. This was a 6 months long observational study. All the provided suggestions of CCP were categorized into- A (drug-drug interaction), B (addition of new drug therapies), C (rational dosing of antibiotics), D (acceleration or deceleration of the doses) and E (adverse drug reaction). Out of total CCP’s 650 suggestions, 566 (87.08%) suggestions were accepted by doctors and modified the therapies, accordingly. CCP being a part of ICU’s multi professional team contribute the professional roles in generating safe, appropriate and quality prescriptions, which finally turns into quality pharmacotherapy for critically ill patients at ICU. Dhaka Univ. J. Pharm. Sci. 18(1): 113-119, 2019 (June)